A pilot investigation of an iOS-based app for toilet training children with autism spectrum disorder. (February 2019) - Mruzek, Daniel W; McAleavey, Stephen; Loring, Whitney A; Butter, Eric; Smith, Tristram; McDonnell, Erin; Levato, Lynne; Aponte, Courtney; Travis, Rebekah P; Aiello, Rachel E; Taylor, Cora M; Wilkins, Jonathan W; et al.
We developed an iOS-based app with a transmitter/disposable sensor and corresponding manualized intervention for children with autism spectrum disorder. The app signaled the onset of urination, time-stamped accidents for analysis, reminded parents to reinforce intervals of continence, provided a visual outlet for parents to communicate reinforcement, and afforded opportunity for timely feedback from clinicians. We compared this intervention with an intervention that uses standard behavioral treatment in a pilot randomized controlled trial of 33 children with autism spectrum disorder aged 3–6 years with urinary incontinence. Parents in both groups received initial training and four booster consultations over 3 months. Results support the feasibility of parent-mediated toilet training studies (e.g., 84% retention rate, 92% fidelity of parent-implemented intervention). Parents used the app and related technology with few difficulties or malfunctions. There were no statistically significant group differences for rate of urine accidents, toilet usage, or satisfaction at close of intervention or 3-month follow-up; however, the alarm group trended toward greater rate of skill acquisition with significantly less day-to-day intervention. Further development of alarm and related technology and future comparative studies with a greater number of participants are warranted.